"Removing the thorns": the role of the arts in recovery for people with mental health challenges. Issue 1 (2nd January 2019) - Gallant, Karen; Hamilton-Hinch, Barbara; White, Cathy; Fenton, Lara; Lauckner, Heidi
Abstract: Background : While the arts have long been associated with mental health, the role of self-directed arts participation in recovery has not been fully explored. Methods : We explored the question: From the perspectives of people living with mental health challenges, how does participation in and exhibiting or performing one's art impact recovery? Six individual interviews and 19 narratives by artists with mental health challenges associated with an arts exhibit were analyzed using inductive thematic analysis. Results : The data are described by the themes providing structure and continuity, (re)creating our personal stories and building community . Novel findings include ongoing engagement in the arts as providing continuity during turbulent times. The role of the arts in advocacy on mental health was highlighted. Conclusion : While artists sometimes perceived paternalism in audience members, the arts provided a powerful means of communicating about mental illness, countering stigma and challenging dominant ways of conceptualizing mental illness.